2012
DOI: 10.3171/2012.7.jns111992
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse brainstem glioma: prognostic factors

Abstract: Object Brainstem gliomas were regarded as a single entity prior to the advent of MRI; however, several studies investigating MRI have recognized that these lesions are a heterogeneous group, and certain subgroups have a better prognosis for long-term survival. The aim of this study was to conduct a retrospective analysis of prognostic factors of patients with brainstem gliomas confirmed by histopathological diagnosis, particularly regarding assessment of whether histological grade, age, and MRI findings are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 21 publications
(17 reference statements)
2
27
0
1
Order By: Relevance
“…Six studies reported use of the ROSA robot [1318] and two the Neuromate robot [12, 19]; the other robots used were the Puma 200 robot [2], Renaissance robot [20], Minerva robot (Swiss Federal Institute of Technology of Lausanne, Switzerland) [21], MKM robot (Zeiss, Oberkochen, Germany) [22], Surgiscope robot (ISIS, Grenoble, France) [23], iSYS1 robot (iSYS, Kitzbühel, Austria) [24], and RONNA G3 robot (University of Zagreb, Croatia) [25]. The size and configuration of the reported devices varied significantly with the ROSA and Neuromate robots, occupying a large footprint and weighing up to 200 kg, and the Renaissance and iSYS1 robots being small enough to fix directly to the patient’s head and Mayfield clamp respectively, and weighing as little as 1.4 kg [20, 24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies reported use of the ROSA robot [1318] and two the Neuromate robot [12, 19]; the other robots used were the Puma 200 robot [2], Renaissance robot [20], Minerva robot (Swiss Federal Institute of Technology of Lausanne, Switzerland) [21], MKM robot (Zeiss, Oberkochen, Germany) [22], Surgiscope robot (ISIS, Grenoble, France) [23], iSYS1 robot (iSYS, Kitzbühel, Austria) [24], and RONNA G3 robot (University of Zagreb, Croatia) [25]. The size and configuration of the reported devices varied significantly with the ROSA and Neuromate robots, occupying a large footprint and weighing up to 200 kg, and the Renaissance and iSYS1 robots being small enough to fix directly to the patient’s head and Mayfield clamp respectively, and weighing as little as 1.4 kg [20, 24].…”
Section: Resultsmentioning
confidence: 99%
“…Dellaretti et al compared transcortical and transcerebellar approaches in patients undergoing brainstem biopsy and did not find any significant difference in outcomes [12]. Nonetheless, given that there is no systematic or objective means of trajectory planning at present, this remains a significant confounding factor.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity for correctly diagnosing low-grade gliomas were quite low with all MR sequences. Multiple studies have tried to establish the role of various MR sequences in predicting survival [20,21,22]. In a large cohort of 100 patients who underwent standard MRI, Dellaretti et al [22] found that in patients assessed by MRI with and without contrast enhancement, mean survival times were 21.7 and 54.2 months, respectively (p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have tried to establish the role of various MR sequences in predicting survival [20,21,22]. In a large cohort of 100 patients who underwent standard MRI, Dellaretti et al [22] found that in patients assessed by MRI with and without contrast enhancement, mean survival times were 21.7 and 54.2 months, respectively (p < 0.001). In a retrospective study, Yamasaki et al [19] showed that clinical and conventional MR findings at presentation were not predictive of survival, although lactate elevation on MRS was a prognostic factor in DIPG patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation